2012
DOI: 10.1111/j.1468-2389.2012.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Applicant Reactions in Saudi Arabia: Organizational attractiveness and core‐self evaluation

Abstract: This paper reports findings from a survey into applicant reactions of working adults in Saudi Arabia. A sample of 193 participants from four job functions was obtained, with measures of organizational attractiveness, core-self evaluation, and applicant reactions to four popular selection methods in the country – interviews, résumés, work sample tests, and references – being included. Findings indicate a notably similar pattern of preference reactions to previous studies in other (Western) countries, affirming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
(101 reference statements)
1
15
0
3
Order By: Relevance
“…In response, there has also been an increasing focus on applicant reactions across countries, with dozens of studies examining similarities and differences in applicant reactions to popular methods comprising selection procedures. Although the North American context still prevails, there has been considerable growth in research in other countries, particularly within Europe (e.g., Anderson & Witvliet, 2008;Bertolino & Steiner, 2007;Hülsheger & Anderson, 2009;Konradt et al, in press;Nikolaou & Judge, 2007), the Middle East (e.g., Anderson, Ahmed, & Costa, 2012), and Asia (e.g., Gamliel & Peer, 2009;Hoang, Truxillo, Erdogan, & Bauer, 2012;Liu, Potočnik, & Anderson, 2016). In fact, since the turn of the millennium, studies have been conducted in more than 30 countries worldwide (Walsh, Tuller, Barnes-Farrell, & Matthews, 2010).…”
Section: Research Trend 3: Sustained and Increased Focus On Internatimentioning
confidence: 99%
“…In response, there has also been an increasing focus on applicant reactions across countries, with dozens of studies examining similarities and differences in applicant reactions to popular methods comprising selection procedures. Although the North American context still prevails, there has been considerable growth in research in other countries, particularly within Europe (e.g., Anderson & Witvliet, 2008;Bertolino & Steiner, 2007;Hülsheger & Anderson, 2009;Konradt et al, in press;Nikolaou & Judge, 2007), the Middle East (e.g., Anderson, Ahmed, & Costa, 2012), and Asia (e.g., Gamliel & Peer, 2009;Hoang, Truxillo, Erdogan, & Bauer, 2012;Liu, Potočnik, & Anderson, 2016). In fact, since the turn of the millennium, studies have been conducted in more than 30 countries worldwide (Walsh, Tuller, Barnes-Farrell, & Matthews, 2010).…”
Section: Research Trend 3: Sustained and Increased Focus On Internatimentioning
confidence: 99%
“…Overall, these studies show interviews and work sample tests to be the most favorable, whereas r esum es, cognitive tests, personality tests, and references are considered as quite favorable methods, and honesty tests, personal contacts, and graphology are the least preferred methods (Anderson et al, 2010). Two recent studies found a similar pattern of applicant reactions (Anderson et al, 2012;Hoang et al, 2012). Based on the reaction generalization assumption, previous research findings, particularly those from Vietnam and Saudi Arabia could serve as an instructive model for China, as these share certain common cultural characteristics.…”
Section: Reaction Generalization Versus Situational Specificitymentioning
confidence: 93%
“…Based on the reaction generalization assumption, previous research findings, particularly those from Vietnam and Saudi Arabia could serve as an instructive model for China, as these share certain common cultural characteristics. For instance, they are all highly collectivistic and place a strong value on personal relationships (Anderson et al, 2012;Chen et al, 2013). However, it is necessary to explore applicant reactions to selection procedures specifically in the context of China to address aspects specific to the Chinese context, such as the use of Guanxi, which are likely to influence applicant reactions and also to advance our knowledge in this field in other Asian countries.…”
Section: Reaction Generalization Versus Situational Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Aday çalışanların başvuru ve alım sürecinde sırasıyla yüz yüze mülakat, özgeçmiş değerlendirmesi ve referans sunulması yollarını tercih ettiği gözlenmiştir (Anderson et al, 2012). Bu bağlamda, Williamson ve ark.…”
Section: Introductionunclassified